Evaluation of the contribution of 16 European beef production systems to food security. (May 2021) - Mosnier, Claire; Jarousse, Anne; Madrange, Pauline; Balouzat, Jimmy; Guillier, Maëva; Pirlo, Giacomo; Mertens, Alexandre; ORiordan, Edward; Pahmeyer, Christoph; Hennart, Sylvain; Legein, Louise; Crosson, Paul; et al.
Abstract: Context: Livestock production, and more particularly ruminants, is criticized for its low conversion efficiency of natural resources into edible food. Objective: The objectives of this paper are to propose an evaluation of the contribution to food security of different European cattle farms through three criteria: 1) food production assessed by the amount of human-edible protein (HEP) and energy (HEE) produced at farm level, 2) feed-food competition at the beef production scale estimated in terms of net human-edible protein and energy and in terms of land used, and 3) food affordability assessed by the production cost of meat, protein and energy. Methods: The analysis is based on 16 representative beef production systems in France, Belgium, Ireland, Italy and Germany and covers cow-calf systems, finishing systems, dairy and mixed dairy- finishing systems, with or without cash crops. Results and conclusions: The results show that, at the farm level, systems producing both beef and milk or cereals have higher HEP and HEE production per hectare (up to 370 kg of HEP and 60, 000 10 6 J.ha −1 ) than specialized beef systems (up to 50 kg of HEP and 1600 10 6 J.ha −1 ) and have lower production costs (approximately €6 kg −1 of HEP in mixed beef system and €29 kg −1 of HEP in a specialized cow-calf-fattener system). Beef systems are almost all HEE net consumers. Results are more variable concerning net HEP efficiency. The cow-calf enterprises are mostly net producers of HEP but, in order to produce human edible meat, these systems need to be combined with finishing systems that are mostly net consumers of HEP. In most cases, cow-calf-finishing systems are net consumers of HEP (between 0.6 and 0.7) but grass-based systems using very little concentrates or systems using co-products not edible by humans are net HEP producers. The grass-based systems use more land area per kilogram of carcass but a major part of this area is non-tilled land, thus these systems are not in direct competition with human food production. The lowest meat production costs are the finishing systems producing the most live weight per livestock unit (LU) per year and dairy systems in lowland which share the costs between milk and meat. Significance: Although most of HEE and HEP efficient farms typically have higher meat production costs, some grassland based systems stand out positively for all indicators. These results pave the way for improvements of the contribution of beef production systems to food security. Graphical abstract: Net Human Edible Protein and Energy Efficiencies of meat production (M_HEP_eff and M_HEE_eff). Notes: M_HEP_eff = HEP of meat HEP of feed and M_HEE_eff = HEE of meat HEE of feed . Calculations are based on farm case studies. Unlabelled Image Highlights: The systems with both beef and milk or cereals produce more protein and energy per ha. Unlike the finishing systems, the cow-calf ones are mostly net producers of protein. Cow-calf-finishing systems using very little concentrates are net protein producers. The grass-based systems use more land area per kg of carcass but mostly non-tilled land. Some trade off exist between meat production cost and feed-food competition.